NeuroVittae: um aplicativo para o cuidado interdisciplinar das necessidades de saúde de pessoas com afasia - Silva, Emilyn Borba da (2020)
Language is a human constitutive activity; it plays a crucial work in all life activities/situations. When aphasia occurs, both written and oral language get compromised in a greater or smaller degree, and also does participation in daily occupation and autonomy. This research aimed to develop an app named NeuroVittae that seeks to improve the autonomous expression of individuals with aphasia about their health conditions and health needs. The research is exploratory and characterized as qualitative and quantitative; the analysis referring to the validation of the app were descriptive, and those referring to the results of the application with the aphasic subjects were supported by the theoretical assumptions that based the creation of the app, in which the language facts (data findings) given in social interaction/interlocution stand out. This research was developed in three phases: 1) scope definition, 2) planning/validation e 3) app implementation. The data collection took place between January 2018 and April 2020. It is noteworthy that the scope was defined through an integrative literature review concerning the evaluation methods that are used by the professionals who work with neurological rehabilitation of adult subjects and/or elderly people with aphasia, published in the last ten years. The results identified the predominance of the use of protocols or evaluations that aim to identify the disabilities that result from brain injury. This literature review reaffirmed the importance of having evaluation procedures that highlight the potentials and the singularities of individuals with aphasia in all dimensions of their lives, that is, the need of procedures with a biopsychosocial approach that capture the expression of their conditions and health needs. The planning phase was based on Luria’s concepts on brain functioning and on other theoretical contributions of Discursive Neurolinguistics. It also relied on the constructs – Activity and Participation – of the International Classification of Disability, Functionality and Health (CIF) and on the document of the American Association of Occupational Therapy – AOTA – Occupational Therapy Practice Structure: domain and process. Twelve professionals/judges collaborated for the validation and final production of the app, four from each area - Physiotherapy, Speech Therapy and Occupational Therapy. Subjects with aphasia also participated. A questionnaire with 12 closed questions on a five-point Likert scale was applied, which evaluated the usability, applicability interface and practicality of the app. The implementation phase took place with the exclusive participation of subjects with aphasia. The NeuroVittae app has a registration section and 134 Activities/Occupations that belong to the following 12 categories: Sensory Experiences, Cognitive Functions, Tasks and general requirements, Communication, Mobility, Self-care, Home life, Interactions and relationships, Financial, Socialization and community life, Security and protection, Sleep and rest. Each of the Activities/Occupations can be analyzed from various materials (visual [photos, icons and writing] and auditory) and functionalities (recording, writing, asking for help). The professionals evaluated positively all the items covered by the app, resulting in an overall Content Validity Index (CVI) of 0.98. The subjects with different aphasic manifestations were able to express their perceptions, conditions and health needs autonomously. The NeuroVittae app can assist in the evaluative and therapeutic processes of subjects with aphasia.